ATTITUDES AND BELIEFS IN A MULTILINGUAL SCENERY - Camacho, Roberto Gomes [UNESP] (2019)
In a multilingual situation, such as the border Ponta Pora/Pedro Juan Caballero, the schooling process and all subsequent linguistic teaching seriously enter into conflict with the degree of literacy as possibly available to Paraguayans students, an exemplary case of fulfillment of a theoretical aspect raised by Street (2007): the dominant character of a culture, which is, in this context, the Portuguese/Spanish-based literacy of Guarani speakers as L1. The hypothesis that we develop here is, therefore, that, as the process of literacy includes attitudes and beliefs shared by students, this inclusive relationship would be a mechanism essential to the development of the formal schooling and social practices of writing and reading, especially when devoid of prejudice arising from the imposition of dominant literacy.